Building assumptions of a research and development center for the monitoring of railway automation. - Radosław Zawierucha (Przegląd Komunikacyjny)
Abstract: The paper describes the initial analysis of the construction of the Research and Development Team (R&D) in the area of cyber security with particular emphasis on data analytics from railway automation systems. The study addresses organizational, technical and business issues. Due to the own experience of the last years of work, this paper is constructed from the operational and organizational perspective of PKP Informatyka. Hence the assumed substantive context, formal, organizational and legislative environment of the expected domain of operation of the research and development team under development. The work describes the tasks, research methods, competences and products of the research team. The project itself is of a project nature - it provides for certain assumptions, adopts selected methodologies and assumes the achievement of specific results.